Comparative mapping in cattle of genes located on human chromosome 18 - Agaba, Morris; Kemp, Stephen J.; Barendse, W.; Teale, A.J. (Springer, 1997)
Human chromosome (Chr) 18(HSA 18) contains approximately 85 million base pains of DNA. Thirty genes and pseudogenes have been mapped to HSA 18 by somatic cell genetics or in situ hybridization. Two bovine genes - Yamaguchi sacroma viral oncogene homology 1 (YESI) and desmocollin type 1 (DSC1) - homologous to HSA 18 loci have been mapped by in situ hybridization to chr 24, and Zoo-FISH analyses show that HSA18 loci are located entirely on BTA24. It is reported here the genomic localization of eight bovine genes homologous to HSA18 genes, ADCYAPI, CDH2, CYB5, DSC2, FECH, NDUFV2, PAI2, and TTR, using somatic cell genetics and linkage analysis in the International Bovine Reference Panel (IBRP).